TAKAYASU ARTERITIS IN A YOUNG FEMALE PRESENTING WITH PYREXIA OF UNKNOWN ORIGIN IN THE PRE-PULSELESS PHASE - Farooq, Abeera; Sheraz, Fatima; Zehra, Tehzeeb; Ali, Hayida; Jahangir adil, Muhammad; Farid, Sheema; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2025)
Takayasu arteritis is a rare chronic large vessel vasculitis that mainly occurs in young females with a higher prevalence in Asian population. This disease, in its early stages, often goes undiagnosed because of its non-specific and vague symptoms. This poses great difficulty for doctors to accurately make the diagnosis. One of its initial presentations is 'pyrexia of unknown origin (PUO). PUO precedes the pulseless stage of Takayasu arteritis. Here we're going to do a case report on a 26-year-old female patient presenting with PUO as the pre-pulseless stage of Takayasu arteritis. The presentation as PUO in the absence of pulse deficits is very uncommon and has been very underwhelmingly reported.